Impact Of Uraemic Xerosis And Pruritus On Quality Of Life Among Maintenance Hemodialysis Patients - Jayabharathy. M, Jayabharathy. M; Devi V, Kalpana; Cecyli.C, Cecyli.C; Keerthana M, Keerthana M; Sri D P, Malini; Devadharshini R, Devadharshini R; Basidh, M. Abdul (Journal of Neonatal Surgery, 2025)
Background: ESRD (end-stage renal disease) is a substantial public health problem, and people endure a vast variety of its symptoms. Uraemic xerosis and pruritus are symptoms in CKD (chronic kidney disease) patients, significantly impairing quality of life. Furthermore, it is an independent risk factor for poorer survival rates. The aim of this study was to evaluate the impact of uraemic xerosis and pruritus on patients' quality of life. Materials and methods: Over the course of six months, 100 hemodialysis patients were chosen for a descriptive, cross-sectional study that was carried out in the hemodialysis unit of ACS Medical College and Hospital. Patients who had prurigo, superficial infections, contact dermatitis, AKI patients, or who were not receiving dialysis for chronic kidney disease were excluded from the study, and the patients were asked to provide informed consent. The EL Gammal severity score, VAS (100mm visual analogue scale), DLQI (Dermatology life quality index), and SF-12 (12-item short form survey) were used to evaluate the intensity of xerosis, pruritus, and quality of life, respectively. Results: Using the generic SF-12 questionnaire, it was shown that hemodialysis patients with end-stage renal disease had a markedly altered quality of life, with reductions observed on both the physical (mean ±SD PCS: 30.60 ± 6.959) and mental (mean ±SD MCS: 28.72 +10.197) components. In our investigation, we found a weak but statistically significant association (p=0.073) between DLQI and the intensity of xerosis and a substantial correlation (p=0.000) between DLQI and pruritus. According to an analysis of demographic characteristics on DLQI and lesional status. Elderly patients also experience a severe deterioration in their quality of life (0.000*). Conclusion: It was determined that maintenance hemodialysis patients' quality of life is negatively impacted by uraemic xerosis and pruritus. Older age was also an aggravating factor for the deterioration of the quality of life.